Association of lipid accumulation product index with self-reported diabetes among residents aged 18 – 44 years in Hebei province, 2020: a surveillance data analysis - Qi QI; Lijuan TANG; Yuhuan LIU; Jinchai GAO; Xiuli NIU; Qianyu LI; Shifan WANG; Xiaoli LIU; Ze CUI (Zhongguo gonggong weisheng)
ObjectiveTo investigate the association between lipid accumulation product (LAP) levels and self-reported diabetes among residents aged 18 – 44 years in Hebei province, and to provide a reference for the prevention and control of diabetes among local residents. MethodsData on 6 373 permanent residents aged 18 – 44 years in Hebei province were collected from the Cardiovascular Disease and Risk Factor Surveillance conducted in 2020. Unconditional multivariate logistic regression models were used to analyze the association between LAP and diabetes risk. ResultsThe median (25th percentile, 75th percentile) of the LAP index was 29.47 (13.67, 62.33) for 3 177 (49.85% of all participants) male residents and 16.58 (9.24, 31.50) for 3 196 (50.15%) female residents. The numbers (percentages) of residents with the LAP index of the lowest, second, third, and highest quartiles were 794 (24.99%), 794 (24.99%), 795 (25.03%), and 794 (24.99%) for men and 799 (25.00%), 799 (25.00%), 797 (24.94%), and 801 (25.06%) for women, respectively. The self-reported prevalence (cases number) of diabetes was 5.60% (178) and 2.85% (91) for men and women. Among residents in the lowest, second, third, and highest quartiles of the LAP index, the self-reported prevalence (number of cases) of diabetes was 0.38% (3), 3.15% (25), 5.28% (42), and 13.60% (108) for men and 0.75% (6), 0.38% (3), 1.88% (15), and 8.36% (67) for women, respectively. After adjusting for age, ethnicity, education level, marital status, employment, annual household income per capita, place of residence, smoking, alcohol consumption, and physical activity, unconditional multivariate logistic regression analysis showed that, compared with those with LAP index in the lowest quartile, male residents with LAP index in the second, third, and highest quartiles had an increased risk of self-reported diabetes, with odds ratios (95% confidence interval) of 7.78 (2.33, 26.01), 12.74 (3.90, 41.63), and 34.38 (10.75, 109.93), respectively, while female residents with LAP index in the highest quartile had an increased risk of self-reported diabetes (odds ratio = 11.32, 95% confidence interval: 4.76, 26.96) compared with those with LAP index in the lowest quartile. ConclusionThere is a positive correlation between the LAP index and the prevalence of self-reported diabetes among residents aged 18 – 44 years in Hebei province. The risk of self-reported diabetes increases with increasing LAP index.